Development of a multi-stage purification process for serum-derived exosomes and evaluation of their regenerative capacity - de Boer, Candice (Department of Surgery, 2020)
Exosomes are secreted membrane vesicles (30-100 nm) found in tissue culture media and various body fluids that have potential as therapeutics and disease biomarkers. Current literature has reported regenerative benefits for blood-derived exosomes but the majority of these studies purified exosomes using ultracentrifugation (UC), a method that has been found to have high levels of protein contamination. Here the regenerative capacity of exosomes isolated by size exclusion chromatography (SEC), a method shown to reduce protein contamination, from human serum was assessed. SEC isolates were found to contain suitably sized vesicles and exosomal markers (CD9, CD81 and TSG101). These isolates allowed for cellular uptake of a range of fluorescent labels and enhanced cellular fibroblast proliferation and endothelial sprout formation in a 3D spheroid-based angiogenesis assay. Further to this, functionality was shown to be retained after incubation of the isolates for 21 days at 37°C. Though a promising indication of regenerative potential, it was found that the isolates contained significant levels of ApoB containing lipoproteins (up to 15 µg ApoB/ml). It was shown that these lipoproteins were predominately the very low and intermediate density lipoproteins. It was found that low-density lipoprotein can impact exosome uptake studies that use fluorescent nucleic acid, protein and lipid dyes. As a substantial extraneous lipoprotein content could also interfere with other downstream applications and analyses such as proteomic analysis, a multistep purification method was developed. A simple 3-step density gradient (DG) UC was introduced prior to SEC that incorporated a high-density iodixanol cushion overlaid by a 18% iodixanol step containing UC concentrated human serum that was then overlaid with 6% iodixanol. This DG relied on flotation to remove lipoproteins. After the multi-step purification (UC DG SEC) ApoB and ApoA1 were not detectable by enzyme-linked immunosorbent assay and western blotting respectively. The UC DG SEC isolates were positive for CD9 and TSG101 and morphologically, as viewed by transmission electron microscopy, had the canonical exosome shape and size. Nanoparticle tracking analysis showed that though exosome marker levels were similar, there were 100 times more particles in SEC purified isolates relative to those from UC DG SEC, emphasising the extent of lipoprotein removal. Proteomic analysis identified 224 proteins in UC DG SEC isolates relative to the 135 from SEC, with substantial increases in exosome-associated proteins and reductions in lipoproteins. The UC DG SEC exosomes still elicited a significant increase in cell proliferation of human dermal fibroblasts but no increase in endothelial sprout formation. After subcutaneous implantation in a rat model, the highly purified exosomes potentially increased an angiogenic response. In conclusion, we show that serum SEC-derived exosomes with much reduced protein content do have regenerative properties but contain contaminating lipoproteins. Our new isolation technique isolated purer serum exosomes that retained cell proliferation stimulation and potentially enhanced an in vivo angiogenic response. This approach should render the isolated exosomes more suitable for biomarker discovery, molecular composition determination and biological function analysis.